1984
DOI: 10.2307/1129920
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Differences in the Comprehension and Production of Narratives by Reading-Disabled and Normally Achieving Children

Abstract: Reading-disabled children's language skills have long been implicated in their poor school performance. This study is a cross-sectional and longitudinal examination of the narrative language skills of both reading-disabled and normally achieving children in an attempt to understand more clearly the language processes involved in these skills and how these processes relate to reading achievement over time. Children were read scriptlike narratives and asked to demonstrate their knowledge of the story by a nonver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 21 publications
5
53
0
1
Order By: Relevance
“…Results of the longitudinal experiment clearly showed that the children with MRD demonstrated difficulty in oral narrative comprehension and production ability compared to the good readers on all three assessment trials. This is consistent with results from previous studies that have investigated aspects of oral narrative ability in children with reading disorders, such as oral narrative comprehension (i.e., the ability to answer questions about a story; Snyder & Downey, 1991) and oral narrative production at macrostructure level (i.e., the number of propositions or action units recalled; Feagans & Short, 1984;Roth & Spekman, 1986;Snyder & Downey, 1991). Results from the current study extend previous research by demonstrating that children with MRD also exhibited weaknesses in microstructure measures of oral narrative ability Note: Oral narrative comprehension: Number of correct answers out of 10 questions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results of the longitudinal experiment clearly showed that the children with MRD demonstrated difficulty in oral narrative comprehension and production ability compared to the good readers on all three assessment trials. This is consistent with results from previous studies that have investigated aspects of oral narrative ability in children with reading disorders, such as oral narrative comprehension (i.e., the ability to answer questions about a story; Snyder & Downey, 1991) and oral narrative production at macrostructure level (i.e., the number of propositions or action units recalled; Feagans & Short, 1984;Roth & Spekman, 1986;Snyder & Downey, 1991). Results from the current study extend previous research by demonstrating that children with MRD also exhibited weaknesses in microstructure measures of oral narrative ability Note: Oral narrative comprehension: Number of correct answers out of 10 questions.…”
Section: Discussionsupporting
confidence: 91%
“…These results not only suggest persistent oral narrative difficulties in children with specific reading disability but also indicate a markedly different relationship between oral narrative ability and reading comprehension performance for children with specific reading disability compared to their typically developing peers. Longitudinal results obtained from a study by Feagans and Short (1984) into the oral narrative comprehension and production abilities of children with specific reading disability provide support to these assumptions. It was found that the children with reading disability demonstrated persistent difficulty retelling a script-like oral narrative compared to their typically developing peers over a 3-year period.…”
Section: Oral Narrative Development In Children With Reading Disabilitymentioning
confidence: 78%
See 1 more Smart Citation
“…Studies indicate that reading retardation is associated with: -use and comprehension of vocabulary (Share et al, 1984;Stanovich, Cunningham, & Feeman, 1984); -use and/or comprehension of morphology and syntax (Donahue et al, 1982;Vogel, 1975;Wiig & Semel, 1986); -production of narratives (Feagans & Short, 1984;Olson & Geva, 1983); -awareness of syntactical and morphological relations (Elbro, 1990;Tunmer, Herriman, & Nesdale, 1988;Torneus, 1990;Vea, 1991); -pragmatic awareness and use of adequate syntax in communicative tasks, i.e. when conveying information to a listener (Donahue et al, 1982); -use of metacognitive strategies and knowledge of story structure in understanding, recalling and producing texts (Short & Ryan, 1984;Wong & Jones, 1982).…”
Section: The Poor Readermentioning
confidence: 99%
“…In conversational situations, LD children are less skilled than nondisabled peers at managing turntaking and initiating conversation and are more likely to defer to others (Donahue, 1983). Feagans and Short (1984) asked reading-disabled children to enact a narrative until it was fully comprehended and then to paraphrase the narrative. Even when comprehension was demonstrated, reading-disabled children of three age groups displayed deficiencies in oral expression on measures of linguistic complexity and content.…”
mentioning
confidence: 99%